2018
DOI: 10.1007/s11356-018-1901-x
|View full text |Cite
|
Sign up to set email alerts
|

The ecological competition and grazing reverse the effects of sulfamethoxazole on plankton: a case study on characterizing community-level effect

Abstract: The toxic effects of sulfamethoxazole (SMX) on densities of two algae, Platymonas helgolandica var. tsingtaoensis, Isochrysis galbana, and of a rotifer, Brachionus plicatilis, were tested by the population and community experiments. Two endpoints, the carrying capacity and the densities array of community in steady state (DACS), were used to characterize the toxic effects at a population level and a community one, respectively. The results showed that the carrying capacity of P. helgolandica var. tsingtaoensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Platymonas helgolandica tsingtaoensis, found widely in saline/brackish waters in the world, are mainly used as a food source in marine aquaculture [17]. It has been reported that some microalgae were supplementary sources of nourishment for aquatic animals, for example, essential amino acids, vitamins, and some essential fatty acids [18,19], and this nourishment could enhance immune function [20].…”
Section: Introductionmentioning
confidence: 99%
“…Platymonas helgolandica tsingtaoensis, found widely in saline/brackish waters in the world, are mainly used as a food source in marine aquaculture [17]. It has been reported that some microalgae were supplementary sources of nourishment for aquatic animals, for example, essential amino acids, vitamins, and some essential fatty acids [18,19], and this nourishment could enhance immune function [20].…”
Section: Introductionmentioning
confidence: 99%